GENERATIVE ARTIFICIAL INTELLIGENCE VS HUMANS IN THE PROCESS OF CREATING CORPORATE IDENTITY ELEMENTS - Kateryna P. Osadcha; Maryna V. Osadcha (Інформаційні технології і засоби навчання)
The emergence of new tools, the appearance of new technologies and improvements to existing ones have resulted in expansion of generative artificial intelligence. The technologies of generative artificial intelligence have already been used by people to perform not only intellectual tasks, but also creative ones, in particular in the field of design. Therefore, their capabilities in graphic design need to be studied. One of the routine tasks of a designer is the development of corporate identity elements (a logo, font, and colour). Designers can spend a lot of time on this, choosing different style options. Therefore, delegating this routine work to generative artificial intelligence may be appropriate. With this practical need in mind, the capabilities of modern AI tools for image and logo generation were studied in the research, and the results of AI logo generation compared to the work of novice designers were analysed. As a result, conclusions were drawn about the expediency of using generative AI technology in the work of designers, in particular, for the development of corporate identity elements, and the appropriateness of studying generative artificial intelligence technology in the training of future designers. These conclusions were made on the basis of a survey of 41 experts in the field of design, information technology and artificial intelligence. Based on the findings of the survey, we can note that it was difficult for experts to distinguish between logos generated by artificial intelligence and logos created by novice designers. Logos developed by novice designers (5) were recognized as the most attractive among the 45 logos presented in the survey. Images generated in some AI tools (Tailor Brands, Hatchful) are considered attractive by design, information technology and artificial intelligence professionals. Therefore, they can be used to create corporate identity elements. Thus, the vast majority of experts agreed that artificial intelligence tools for generating images and logos should be used in the process of creating corporate identity elements. In addition, the vast majority of experts found it advisable to use generative artificial intelligence technologies in the process of professional training of future designers.